Catalytic reforming of tar during gasification. Part II. Char as a catalyst or as a catalyst support for tar reforming - Min, Zhenhua; Yimsiri, P.; Asadullah, Mohammad; Zhang, Shu; Li, Chun-Zhu (Elsevier Science Ltd, 2011)
Char, char-supported catalysts and ilmenite were investigated for the steam reforming of biomass tar derived from the pyrolysis of mallee wood in situ. Special attention was given to the reforming of aromatic ring systems in tar. The results indicated that the char-supported iron/nickel catalysts exhibited much higher activity for the reforming of tar than the char itself. Ilmenite and the char-supported iron catalyst contained similar active phase but showed different tar reforming activities. Kinetic compensation effects demonstrated that the reaction pathways on the char-supported catalysts were similar but were different from those on ilmenite. The proprieties of support could play important roles for the activities of the catalysts and the reaction pathways on the catalysts. Char would not only disperse the catalysts but also interact with the catalysts to enhance their activity for the steam reforming of tar.